If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1X + -90 = 50 + -4X Reorder the terms: -90 + -1X = 50 + -4X Solving -90 + -1X = 50 + -4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '4X' to each side of the equation. -90 + -1X + 4X = 50 + -4X + 4X Combine like terms: -1X + 4X = 3X -90 + 3X = 50 + -4X + 4X Combine like terms: -4X + 4X = 0 -90 + 3X = 50 + 0 -90 + 3X = 50 Add '90' to each side of the equation. -90 + 90 + 3X = 50 + 90 Combine like terms: -90 + 90 = 0 0 + 3X = 50 + 90 3X = 50 + 90 Combine like terms: 50 + 90 = 140 3X = 140 Divide each side by '3'. X = 46.66666667 Simplifying X = 46.66666667
| -17-3= | | 3/6-x=2 | | -30=5(2x-2)-6x | | 6=k/9 | | 4x+9+5x=108 | | 16h=8(2h+(-10)) | | c/4+1=8 | | 96=80+r | | X+(x+0.15)p+(p+0.15)=40 | | -9(6+h)=2h-10 | | 3=x-2x+3 | | -2(x-5)=12-3x | | -3x+5=9 | | 8(x-8)=2+7x | | 1.2x=0.6x | | -2(-7k+4)=-22 | | 6=-2(x+7)+4x | | 1=x-3x+7 | | (3x+5)+3=-6(2x-1) | | n/66=17 | | 3x-8-x=-8 | | -2/5I=13/5 | | (1+8i)+4+(i)= | | -3/5x+2 | | 3(x-4)=58 | | 3(c+0.3333)=4 | | 9(c+5)=8c-2 | | 43=7x-3x+7 | | 44+4567876543=z | | 10x+3(-2X+6)=-6 | | M-4=16 | | 6(2x+3)=-42 |